Object-Oriented Analysis and Design : A Pragmatic Approach - Deacon, John (Noida, India Pearson, 2015)
This approach to object-oriented analysis and design demonstrates how to lay the foundations for developing the best possible software. The focus of the text is on typical development projects and technologies, showing exactly what the different development activities are, and emphasising what they should and should not be trying to accomplish.
Include Figures, Glossary and Index.
A Pragmatic Approach.
Keywords: Object-oriented methods (Computer science) -- Object-oriented programming (Computer science) -- System analysis -- System design